DEMOKRASI SOSIAL DALAM PEMIKIRAN PAUL FEYERABEND - Widarda, Dodo (TEMALI : Jurnal Pembangunan Sosial, 2019)
This article reevaluates Feyerabend’s thought in formatting social order based on his concept of Anything Goes. The discussion is a new challenge for social studies in the new circumstances and time. By taking Feyerabend’s books this study describes and analyzes the format of Feyerabend’s thought, what are being rejected by him, and what is being proposed by him in order to develop democracy in the community. By his effort, it is clear that Feyerabend places democracy as his fundamental reference for his idea of intellectual movement. Finally, this article contextualizes Feyerabend’s thought with what being happened in our time.